2013
DOI: 10.1038/onc.2013.486
|View full text |Cite
|
Sign up to set email alerts
|

Ras regulates kinesin 13 family members to control cell migration pathways in transformed human bronchial epithelial cells

Abstract: We show that expression of the microtubule depolymerizing kinesin KIF2C is induced by transformation of immortalized human bronchial epithelial cells by expression of K-RasG12V and knockdown of p53. Further investigation demonstrates that this is due to the K-Ras/ERK1/2 MAPK pathway, as loss of p53 had little effect on KIF2C expression. In addition to KIF2C, we also found that the related kinesin KIF2A is modestly upregulated in this model system; both proteins are expressed more highly in many lung cancer cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 56 publications
1
34
0
Order By: Relevance
“…We recently found that KIF2A and the closely related kinesin KIF2C are both up-regulated in many cancers and that their persistent expression is supported by oncogenic K-Ras and ERK1/2 (19). As previously found in HeLa and 293 cells, depletion of KIF2A from HBEC3KT prevented typical lysosomal organization, and mTOR also remained diffuse and less well-localized with lysosomes ( Fig.…”
Section: Significancesupporting
confidence: 51%
See 4 more Smart Citations
“…We recently found that KIF2A and the closely related kinesin KIF2C are both up-regulated in many cancers and that their persistent expression is supported by oncogenic K-Ras and ERK1/2 (19). As previously found in HeLa and 293 cells, depletion of KIF2A from HBEC3KT prevented typical lysosomal organization, and mTOR also remained diffuse and less well-localized with lysosomes ( Fig.…”
Section: Significancesupporting
confidence: 51%
“…mRNAs encoding KIF2C and, to a lesser extent, KIF2A are decreased in both HBEC3KT and HBEC3KTRL53 by extended exposure to PD0325901, which inhibits the enzymes MEK1 and MEK2 that activate ERK1/2 (19). These and other studies indicated that ERK1/2 stimulate KIF2A/C expression.…”
Section: Inhibition Of the Erk1/2 Pathway Alters Lysosome Positioningmentioning
confidence: 56%
See 3 more Smart Citations